2018
DOI: 10.1021/acs.iecr.8b02464
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Corncob-Based Solid Acid Catalyst for Biodiesel Production

Abstract: In the present study, highly efficient catalysts based on corncob were synthesized for the esterification process. The synthesized catalysts were characterized by BET, XRD, and FT-IR. The effect of catalyst impregnation, carbonation, and sulfonation was studied in detail. The highest conversion of oleic acid (∼94.4%) was observed using a catalyst synthesized at H 3 PO 4 impregnation ratio = 1 and time = 5 h; carbonization temperature = 723 K and time = 8 h; sulfonation temperature = 393 K and time = 15 h. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 80 publications
(221 reference statements)
1
21
0
Order By: Relevance
“…The reusability of the corncob‐based SCC in the oleic acid esterification was also conducted at 65 °C for 20 cycles by using methanol, ethanol, n ‐hexane as regeneration agents. [ 123 ] The outcome of the study evidenced the excellent stability of the catalyst regenerated by n ‐hexane, where ∼90% oleic acid conversion was achieved for each cycle with only insignificant decline in activity as shown in Figure 11 . It was observed that the catalyst performance of glucose‐based SCC maintained FFA conversion at 76% for five consecutive cycles during the PFAD esterification and declined to <70% after the sixth cycle [38c] .…”
Section: Reusability Of the Sulfonated Carbon‐based Catalysts For Biodiesel Productionmentioning
confidence: 94%
See 1 more Smart Citation
“…The reusability of the corncob‐based SCC in the oleic acid esterification was also conducted at 65 °C for 20 cycles by using methanol, ethanol, n ‐hexane as regeneration agents. [ 123 ] The outcome of the study evidenced the excellent stability of the catalyst regenerated by n ‐hexane, where ∼90% oleic acid conversion was achieved for each cycle with only insignificant decline in activity as shown in Figure 11 . It was observed that the catalyst performance of glucose‐based SCC maintained FFA conversion at 76% for five consecutive cycles during the PFAD esterification and declined to <70% after the sixth cycle [38c] .…”
Section: Reusability Of the Sulfonated Carbon‐based Catalysts For Biodiesel Productionmentioning
confidence: 94%
“…SCC derived from sugarcane bagasse, [ 42,92 ] glucose, [38b-d] oil palm EFB, [36a] palm seed, [ 48 ] corncob, [ 122,123 ] palm kernel shell, [ 2 ] bamboo, [ 2 ] cow dung, [ 41 ] bituminous coal, [ 112,124,125 ] murumuru kernel shell, [ 93 ] and orange peel [ 45 ] have been used in the esterification of PFAD previously. Nonedible PFAD is produced as a by‐product in the oil palm processing factories in the fatty acid deodorization and stripping stages.…”
Section: Catalytic Applications Of Sulfonated Carbon‐based Catalysts In Biodiesel Productionmentioning
confidence: 99%
“…A number of reports published demonstrate increased solid acid heterogeneous catalysts doped with sulfated oxides. For example typical solid superacids such as SO 4 2– /ZrO 2 , SO 4 2– /TiO 2 , SO 4 2– /TaO 5 , SO 4 2– /Nb 2 O 5 [ 66 , 69 , 263 , 312 – 314 , 316 , 319 , 320 ]. Table 9 is a summary showing modified metal oxides doped with sulfated metal oxides for the production of biodiesel.…”
Section: Production Of Biodiesel With Acid and Base Heterogeneous Catalystsmentioning
confidence: 99%
“…There are two common ways of sulfonation on corn cob as acid catalyst preparation, reflux system, and thermal treatment using an autoclave Teflon reactor. These two methods have a different effect on BET surface area and pore properties of catalyst [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. Ibrahim et al [53] found that the surface area of solid catalysts before and after sulfonation by using a reflux system was almost identical, i.e.…”
Section: Current Problem Of Homogeneous Catalyst For Biodiesel Productionmentioning
confidence: 99%
“…It was due to the insertion of -SO3H groups on the surface. Hussain and Kumar [59] reported the change of surface area before and after sulfonation of corncob-derived heterogeneous catalyst in which the surface area decreased after sulfonation from 1268 m 2 .g -1 to 641 m 2 .g -1 . They claimed that the decrease on surface area after sulfonation indicated that the -SO3H groups successfully grafted onto surface, which acted as the active sites.…”
Section: Current Problem Of Homogeneous Catalyst For Biodiesel Productionmentioning
confidence: 99%